Schindler's list [videorecording (Blu-Ray)] - Zaillian, Steven; Neeson, Liam; Kingsley, Ben, 1943-; Fiennes, Ralph; Goodall, Caroline, 1959-; Sagalle, Jonathan; Davidtz, Embeth, 1966-; Keneally, Thomas (Universal Pictures Home Entertainment, 2018)
Commemorate the twenty fifth Anniversary of Steven Spielberg's cinematic masterpiece of one of the most historically significant films of all time Winner of seven Academy Awards including Best Picture and Director, this incredible true story follows the enigmatic Oskar Schindler, who saved the lives of more than 1,100 Jews during the Holocaust. It is the triumph of one man who made a difference and the drama of those who survived one of the darkest chapters in human history.